2017
DOI: 10.3390/ijms18010174
|View full text |Cite
|
Sign up to set email alerts
|

Glycative Stress and Its Defense Machinery Glyoxalase 1 in Renal Pathogenesis

Abstract: Chronic kidney disease is a major public health problem around the world. Because the kidney plays a role in reducing glycative stress, renal dysfunction results in increased glycative stress. In turn, glycative stress, especially that due to advanced glycated end products (AGEs) and their precursors such as reactive carbonyl compounds, exacerbates chronic kidney disease and is related to premature aging in chronic kidney disease, whether caused by diabetes mellitus or otherwise. Factors which hinder a suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…AGE precursors including methylglyoxal and glyoxal are degraded by enzymes, such as glyoxase-1 (Glo-1), and eliminated from the body through the kidney [ 15 , 27 ]. Some previous reports have shown that activation of Glo-1 produces renal protective effects.…”
Section: Carbohydrate Metabolism and Ckdmentioning
confidence: 99%
“…AGE precursors including methylglyoxal and glyoxal are degraded by enzymes, such as glyoxase-1 (Glo-1), and eliminated from the body through the kidney [ 15 , 27 ]. Some previous reports have shown that activation of Glo-1 produces renal protective effects.…”
Section: Carbohydrate Metabolism and Ckdmentioning
confidence: 99%
“…Clinical studies have shown that short periods of poor glycemic control might induce irreversible pathophysiological changes in several organs including the kidney, despite subsequent good glycemic control. This phenomenon is called metabolic memory [1,2]. Important mediators for this metabolic memory may be advanced gly-cation end products (AGEs), potentially involved in the dysregulation of epigenetic structures [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is called metabolic memory [1,2]. Important mediators for this metabolic memory may be advanced gly-cation end products (AGEs), potentially involved in the dysregulation of epigenetic structures [1,3]. The formation of AGEs is caused by hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors are involved in the genesis and progression of urological malignancies, including hypoxia, hormone influence, genetic predisposition, oxidative and glycative stresses and inflammation [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. With regards to oxidative stress, glycative stress and inflammation, a complex interplay is known to exist between these biological phenomena, so that each of them fuels the other in a fine-tuned regulatory circuitry.…”
Section: Introductionmentioning
confidence: 99%